If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 2z + 4 Reorder the terms: 16 = 4 + 2z Solving 16 = 4 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 16 + -2z = 4 + 2z + -2z Combine like terms: 2z + -2z = 0 16 + -2z = 4 + 0 16 + -2z = 4 Add '-16' to each side of the equation. 16 + -16 + -2z = 4 + -16 Combine like terms: 16 + -16 = 0 0 + -2z = 4 + -16 -2z = 4 + -16 Combine like terms: 4 + -16 = -12 -2z = -12 Divide each side by '-2'. z = 6 Simplifying z = 6
| 2y=2y(y-1) | | -5(x-4)=-6(x+8) | | 2y+-3=50 | | 16+2n=-58 | | 9x-32=-5x+52 | | 400-15x=-5000 | | 5r=170 | | 3+3h=18 | | 18-13+n=9 | | (2k^2)-12=12k | | 4+2g=14 | | .01(x+7)=3.5 | | 9+3d=15 | | -7c=53 | | 4*-16-6y=50 | | 25=5x+2 | | 20=3r+2 | | 9r+7=21r+10 | | y=3/4*-16-7 | | x^2/(0.2-x)=0.17 | | (4n+11)+(8n+22)=195 | | 2x+x=63 | | 4*-184-6y=50 | | -5(3y-5)+4(2y+10)= | | 4/9x=2 | | 5-n=7-2n | | y=3/4*-184-7 | | 2s^2-3s-20= | | c(3a+b)= | | y=3/4*-114-7 | | 15x-9=11x-35 | | (4y-10)+3x=190 |